A Critical Review on Ambupana - Upadhye, Gandhali; Shikerkar, Dr. Pratima (International Research Journal of Ayurveda & Yoga, 2014)
Ambu or Udaka is fundamental for the conservation of life of all the living beings. It is considered as Prana, Jeevana and has been equated to the qualities of Amruta. It is superior amongst all the Anupanas. Water is a source of health only if taken at right time and in appropriate quantity. In the present epoch, several times it has been noted that people are forced to consume a particular amount of water without accessing the Desha, Kala, Prakriti etc. As per the Ayurvedic classics Atyambupana or Mithya-jalapana is a prime causative factor for various serious disorders. In this current article an attempt has been made to review all the aspects of Ambupana as per Ayurvedic literature.